The challenges of digital governance in the Regions: Study in Central Lampung Regency, Indonesia - Mukhlis, Maulana; Makhya, Syarief; Yulianto, Yulianto; Aviv, Muhammad (Goodwood Publishing, 2025)
Purpose: Adopting digital technology in government processes is believed to improve a state's administration. Almost any change management theory emphasizes the importance of technology as one of the main components to address whether an organization, including public organizations has the ability to win competitions. Digital technology adoption for public services responds to inefficiency, participation frustration, and minimum collaboration and service innovation. This paper investigates the application of digital technology in an integrated digital government modernization, its implications, and challenges in creating expected public values in the Middle Lampung Regency, Indonesia. Methods: This qualitative study involved informants with authority in regional digital government administration. Data were collected through interviews and document analysis. Data were analyzed by using a descriptive content analysis procedure. Results: The results show that although digital government services have been implemented in various types of public services, they are not integrated with public service business processes so digital service applications spread across various types of services cannot be integrated properly. Limitations: There are gaps between applications and service qualities, including fraud in some cases. Contributions: The digital government that is expected to be the optimal method for improving innovation, value, and public service quality cannot be implemented quickly because of complex challenges that must be addressed.